Legal Analysis of the Application of Restorative Justice in Corruption Cases Based on the Circular Letter of the Deputy Attorney General for Special Crimes - Muhamad Nur, Newaldy Fatiha; Sunggara, M. Adystia; Pratama, M. Ilham Wira (IHSA Institute, 2025)
This study discusses the application of restorative justice principles in corruption cases based on Circular Letter of the Deputy Attorney General for Special Crimes Number B-765/F/FD/04/2018. The emergence of this policy is one of the alternative efforts to resolve small-scale corruption cases more efficiently, namely through the recovery of state losses without having to go through a lengthy legal process. This study aims to analyze the extent to which the principles of restorative justice have been applied and to identify various obstacles encountered in its implementation. The method used is normative legal research with a legislative and conceptual approach. The results of the study indicate that although this approach provides opportunities for faster recovery of state losses, its implementation still faces various obstacles, such as the lack of a strong legal basis in anti-corruption laws, concerns about abuse of authority, and resistance from the public because it is perceived as reducing the deterrent effect. Therefore, regulatory updates and strict oversight are needed to ensure that this policy is implemented fairly, transparently, and maintains the integrity of corruption eradication efforts